Problem based learning and software simulation tools: a case of study in computer science first year students - Giacomantone, Javier (2009)
In this work an adapted problem based learning strategy is presented for the particular case of rst year computer science university students. A pilot study was conducted to determine the validity of the proposed alternatives in one particular undergraduate course, Computer Organization. The main problems detected in rst year students involve de ciencies in the learning process, resulting in a lack of critical thinking and problem solving skills that are essential in Computer Science related disciplines. The main objective of testing di erent models, through problem based oriented learning alternatives and intensive use of simulation software, was to assess how students develop self learning, problem analysis, problem solving and communication skills.